THE ROLE OF VIDEOS IN ESP MATERIAL DEVELOPMENT:A THEORETICAL FRAMEWORK - Haydarova Shahrizoda (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This academic paper offers a thorough examination of video integration in ESP curriculum design by combining theoretical frameworks from applied linguistics and educational psychology with useful classroom applications. By relating Paivio’s dual coding theory and CLT principles to the particular requirements of profession-oriented language instruction, the author builds a solid theoretical framework. The work is especially beneficial since it treats opportunities and obstacles in a balanced manner, including both the practical limitations faced by educators and the cognitive and motivational advantages of video-based learning.The suggested three-phase activity structure (pre-, while-, and post-watching) provides practitioners with practical advice. The discussion of VR and AI technologies in the future places the research in the context of current developments in education’s digital transformation. Suggested for scholars interested in multimedia-assisted language learning and professional communication training, ESP curriculum designers, and language instructors in academic and professional contexts.